NEEDS ANALYSIS OF ANDROID-BASED MEDIA ABOUT DNA REPLICATION MATERIALS AT UNIVERSITIES - Yolanda Ruhul Azomi; Yuni Ahda; Relsas Yogica; Dwi Hilda Putri; Syamsurizal Syamsurizal (ATRIUM PENDIDIKAN BIOLOGI, 2022)
The development of science and technology has an important role in the process of improving the quality of education, one of which is by creating a learning medium that can support the learning process. The purpose of this study was to determine the needs of students for Android-based learning media on DNA replication material for genetics courses in the Department of Biology, Faculty of Mathematics and Natural Sciences, UNP. This type of research is a quantitative descriptive study. The method used in data collection was carried out by distributing questionnaires to biology students who had taken genetics courses and interviewing two lecturers in the genetics course. In addition, the data used are in the form of study results obtained by students who have completed the genetics course. The results showed that students experienced difficulties in understanding the DNA replication material due to the abstract material and the lack of interesting learning media. For this reason, an Android-based learning media is needed that can be accessed anywhere and anytime to support student learning.